Enlargement and Integration Workshop “Digital Transformation, Data and AI in the Western Balkans” - Trenovski, Borce; Tomikj, Ana; Merdzan, Gunter (Publications Office of the European Union, 2022)
Banks are the key technological enablers of digital transformation in the finance sector in North Macedonia. Digitalization contributes to easier and faster access to a wide range of products and services, which in turn stimulates the growth of non-cash payments. In 2020 there is a significant increase in the usage of e-banking by customers and a 121% increase in paying online with a card. Quantitative analysis will be based on secondary data resources, involving available databases, research papers, books, and national and international economic organisations' reports.
What Drives the Digital Transformation in the Western Balkan Banking Sector? – The Case of North Macedonia